The purpose of solving an algebraic expression in an equation is to find the unknown variable. When two expressions are equated, they form an equation and therefore, it becomes easier to solve for the unknown terms. To solve an equation, place the variables on one side and the constants on the other side.
Sure hope this helps
1 + 1x
OR
1 + x
They mean the same thing! Hope this helps!
Substitute the x for 5, so your equation would be 2(5)-4
(X x 6) = (X x 8) -4
Ps. Make sure yoi dont times the (X x 8) by -4 the -4 is by itself.
I personally found it easier thinking if there is a difference of 4 between 6 x X and 8x X then it must be 2x2 as the difference between 6 and 8 is 2. therefore 4 divided by 2 = 2 and 2 x 2 = 4
Therefore x = 2
Step-by-step explanation:
General equation: y = 2 + c/(x - 1)
When x = 4, y = 4.
=> (4) = 2 + c/(4 - 1), c = 6.
Hence the equation is y = 2 + 6/(x - 1).